2012
DOI: 10.1021/je200886j
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of 1-Butyl-3-methylimidazolium Tetrafluoroborate/N-Methyl-2-pyrrolidone Mixtures and the Solubility of CO2 in the System at Elevated Pressures

Abstract: Densities and viscosities of 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4]) (1) + N-methyl-2-pyrrolidone (NMP) (2) with w 1 = 0.0000, 0.5000, 0.6999, 0.8981, and 1.0000 at T = (298.15 to 318.15) K were measured and fitted to standard equations. The results show that densities and viscosities of the hybrid solvents decrease with the increase of temperature and mass fraction of NMP. A high-pressure variable-volume view cell technique was used to determine the solubility of CO2 in pure solvents and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…They are nonflammable in the liquid state in a wide range of temperatures, low or non-toxic, of a high chemical stability, high ionic conductivity and able to dissolve numerous organic, inorganic and organometallic compounds [ 25 ]. In addition, ILs are environmentally-friendly solvents in addition to being excellent absorbents of when added to other specific solvents [ 26 , 27 ]. Therefore, they are considered to be essential for green chemistry synthesis and have attracted much attention as potential alternatives to conventional volatile organic-solvent systems.…”
Section: Introductionmentioning
confidence: 99%
“…They are nonflammable in the liquid state in a wide range of temperatures, low or non-toxic, of a high chemical stability, high ionic conductivity and able to dissolve numerous organic, inorganic and organometallic compounds [ 25 ]. In addition, ILs are environmentally-friendly solvents in addition to being excellent absorbents of when added to other specific solvents [ 26 , 27 ]. Therefore, they are considered to be essential for green chemistry synthesis and have attracted much attention as potential alternatives to conventional volatile organic-solvent systems.…”
Section: Introductionmentioning
confidence: 99%
“…15) K under atmospheric pressure, in continuation of our previous work [11]. Imidazolium based ILs can be used for extractive desulfurization of liquid fuels, mainly with regard to those S-compounds that are very complicated to eliminate by common hydrodesulfurization (HDS) process.…”
Section: Introductionmentioning
confidence: 78%
“…The Provenance, CAS number, water content, mass fraction purity, purification method and analysis method of the compounds are given in table 1. The purity of the chemicals is ascertained by comparing the experimental values of density, refractive index and speed of sound at temperatures T = (298.15 to 323.15) K with the literature (Table 2) [11,[14][15][16][17][18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…To be specific, S is similar with the parameter in Bara’s work and refers to the moles of CO 2 by per liter absorbent. These properties of commercial solvents, , ionic liquids, , and some polymer-based absorbents ,,, were compared with those of PC + PPGME340 studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…They found that CO 2 absorption capacity and kinematic viscosity decrease with the addition of water into PEG200. Similarly, to improve the application of ionic liquid for gas treatment, hybrid absorbents using ionic liquids blended with common organic solvents or water were widely studied. …”
Section: Introductionmentioning
confidence: 99%